Kompetensi Penelitian Dosen dalam Meningkatkan Publikasi Ilmiah Era Digital (Studi Kasus dalam Konteks Pendidikan Umum/Karakter) - H. Soro, Suharyanto (LP. Ma'arif Janggan Magetan, 2024)
Research competency is a mandatory element for a lecturer to have as a concrete form of knowledge applied in academic life. Lecturers are professional educators and scientists who carry out the tridharma activities of higher education, namely, learning activities both in the classroom and in the classroom, research activities in order to develop and give birth to new knowledge, and community service activities. This research aims to formulate lecturer competencies and scientific publications in the digital era. Researchers use a qualitative research paradigm with a case study approach. The sample in this research were lecturers with doctoral degrees and the functional academic position of lecturer. They live on the island of West Java, Indonesia. The research results show that (1) A lecturer has six competencies, namely pedagogical, professional, research, service, personality and social competencies; (2) Lecturers conduct research at least twice a year, to increase productivity/scientific publications in the digital era; (3) The digital era provides distinct advantages for lecturers, namely ease of access to information, in the form of data collection, data analysis, and publication of research results, both print and digital, displaying attractive forms.